2018
DOI: 10.1371/journal.pone.0199675
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CIP2A expression in solid tumors: A meta-analysis

Abstract: CIP2A, cancerous inhibitor of protein phosphatase 2A, was initially recognized as an oncoprotein. Recently several studies revealed that CIP2A could function as a prognosis biomarker, however, the result remained not comprehensive, partly due to small number of patients included individually. Here we carried out a meta-analysis of published studies to assess the prognostic significance of CIP2A in solid tumors. All eligible studies were identified through searching PubMed, Embase and Web of Science database. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In addition, upregulation was significantly associated with features of poor prognosis, such as the large tumor size, cervical lymph node involvement, undifferentiated tumors, and advanced clinical stage. Our observations were verified in OSCC [27], NPC [28], breast [31], non-small cell lung cancer (NSCLC) [34], and many other malignancies [35].…”
Section: Discussionsupporting
confidence: 60%
“…In addition, upregulation was significantly associated with features of poor prognosis, such as the large tumor size, cervical lymph node involvement, undifferentiated tumors, and advanced clinical stage. Our observations were verified in OSCC [27], NPC [28], breast [31], non-small cell lung cancer (NSCLC) [34], and many other malignancies [35].…”
Section: Discussionsupporting
confidence: 60%
“…Accumulating evidence indicates that CIP2A overexpression is associated with poor survival in patients with solid tumors and may serve as a predictive factor of poor prognosis. 10,15,25 Preclinical in vitro and in vivo studies have shown that CIP2A may regulate the proliferation, senescence, and apoptosis of multiple cancer cells [26][27][28] and contribute to resistance to chemotherapy such as cisplatin or docetaxel in solid tumors. [29][30][31] Therefore, CIP2A inhibition may serve as a promising modality to overcome chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value for CIP2A, a direct inhibitor of a tumour suppressor PP2A, has been reported in wide range of human solid tumours (14); however, its association with human leukaemia has not yet been clarified. To assess the expression level of CIP2A and its downstream target PP2A in AML and also to explore its plausible contributory role in leukomogensis, peripheral blood of 30 AML patients (56% male and 44% female) with the median age of 49 years old were collected for quantitative real-time PCR analysis.…”
Section: The Expression Level Of Cip2a and Pp2a In Aml Samplesmentioning
confidence: 99%